(untitled) (Experimental biology, 2024)
The question of the origin of the psyche is one of the fundamental questions in biology and psychology. The answer to it is inextricably linked with an understanding of what the psyche is in general. The objective of this article is to answer the question of when and how the psyche appeared in evolution, and thereby clarify the concept of the psyche. In the article methods of theoretical analysis, generalization and mental modeling are used. Not all living organisms have a psyche; this method of interaction with the world appears at a certain stage of evolution and is provided by a nervous system that has reached the required level of complexity. The psyche first appears in nature with the emergence of sensitivity (in the form of sensations). Sensations are the mental process of establishing conditioned connections between unconditioned and conditioned stimuli. At the physiological level, conditioned connections are provided by conditioned reflexes. Conditioned reflexes require the presence of a nervous system of a certain degree of development. The earliest animals with a nervous system that meets the minimum requirements are apparently flatworms. These organisms can be considered as a starting point for the appearance of the psyche in the evolution. The psyche is a stage on the biological evolutionary path of development of the forms of reflection and interaction used by organisms. Consideration of the nature of the psyche in conjunction with biological data allows us to more clearly outline boundaries, understand essence and describe the origin of the psyche.